2006
DOI: 10.1007/s00221-006-0457-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of prefrontal cortex in visuo-spatial planning: a repetitive TMS study

Abstract: The visuo-spatial planning process is based on an "opportunistic" combination of heuristics and strategies, carried out in small units during the execution of plans. In order to investigate the functional role of the prefrontal cortex in heuristic switching, 42 healthy controls performed a labyrinth crossing task (the Maps Test). During this computerized version of the Travelling Salesperson Problem, subjects had to decide which order of locations optimizes total travel time and distance. This task was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 24 publications
0
36
0
1
Order By: Relevance
“…Participants use keyboard arrow keys to move a cursor along roads to indicate a path between points. Using the Maps task, Basso and colleagues have reported results indicating that people may switch among several heuristics during the process of a single solution, and that inhibiting switching results in performance decrements (Basso et al, 2006;Cutini et al, 2008). Recent research from this group has also reported gender differences (Cazzato et al, 2010).…”
Section: Instructional Variants Of Tspsmentioning
confidence: 92%
See 2 more Smart Citations
“…Participants use keyboard arrow keys to move a cursor along roads to indicate a path between points. Using the Maps task, Basso and colleagues have reported results indicating that people may switch among several heuristics during the process of a single solution, and that inhibiting switching results in performance decrements (Basso et al, 2006;Cutini et al, 2008). Recent research from this group has also reported gender differences (Cazzato et al, 2010).…”
Section: Instructional Variants Of Tspsmentioning
confidence: 92%
“…Basso, Bisiacchi, and colleagues have used a variation of the standard TSP referred to as the Maps test. The main purpose of the research has been to identify how heuristics are used by human solvers and how this may be affected by brain damage or other forms of functional impairment (Basso et al, 2001;Basso et al, 2006). These latter findings will be described later, while in the present section we will describe the task itself and some…”
Section: Instructional Variants Of Tspsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding potential concerns related to TMS, it has the potential to better explain the occurrence of phenomena in consumer research: an example of a TMS study that would have relevance for consumer research is an experiment conducted by Basso et al (2006). They used repetitive TMS to investigate the role of the prefrontal cortex in visuospatial planning.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…In recent years cognitive scientists have begun to examine human performance in optimization tasks and, although still in its infancy, this new research area has attracted the attention of researchers working in vision (Findlay & Brown, 2006), memory (Kong, Schunn, & Wallstrom, 2010), decision making (Ragni & Löffler, 2010), clinical neuroscience (Basso et al, 2006) and comparative psychology (Gibson, Wasserman, & Kamil, 2007). Preliminary findings reported in the psychological literature indicated that untrained human subjects can quickly produce optimal or near-optimal solutions to TSPs, and often outperform simple approximating algorithms, such as the nearest neighbour procedure (MacGregor & Ormerod, 1996).…”
Section: Introductionmentioning
confidence: 99%